Narrative Review of the Theoretical-Methodological Foundations of the TREINI Program - Renato Guimarães Loffi; Deisiane Oliveira Souto; Thalita Karla Flores Cruz; Arthur Felipe Barroso de Lima; Fabiana Rachel Martins Costa Rocha; Simone Rosa Barreto; Patrícia Aparecida Neves Santana; Amanda Aparecida Alves Cunha Nascimento; Vitor Geraldi Haase (MDPI AG, 2024)
Scientific knowledge has advanced in the implementation of safe and beneficial interventions for children and adolescents with cerebral palsy (CP). Although the importance of interdisciplinary interventions that integrate all components of the International Classification of Functioning, Disability and Health (ICF) into family-centered practices is widely recognized, this approach is not yet widely adopted. Instead, many programs remain focused on isolated domains. This study presents the theoretical and methodological foundation of TREINI, an interdisciplinary and family-centered program developed for children and youth with CP and other neurodevelopmental disorders. TREINI incorporates intervention strategies that address all ICF domains. It is grounded in the biopsychosocial model of health and utilizes principles based on the best evidence in pediatric rehabilitation, including intensive training, task-oriented training, and a naturalistic learning environment. Unlike traditional rehabilitation approaches, the care provided by the TREINI program is delivered through an intensive and interdisciplinary approach, by a team working collaboratively in a single location. In addition to including evidence-based interventions, the TREINI program features two innovative components: the "City of Tomorrow", a naturalistic learning environment, and the "TREINI Exoflex" therapeutic suit, specifically designed to address deficiencies in the body functions and structures of children with CP and other neurodevelopmental disorders. This program has been carefully designed to support the process of neurological re-education and rehabilitation for children and adolescents with neuropsychomotor developmental delays.